Crescimento gengival em indivíduos transplantados renais sob os regimes imunossupressores de ciclosporina, tacrolimus e sirolimus: Polimorfismo genético (+3954 C/T) do gene da interleucina- 1beta e avaliação clínica após 44 meses - Lidiane Cristina Machado Costa (2012)
Prospective studies that compare the changes in the gingival status of renal transplant patients under immunosuppressive regimens based on cyclosporine (CsA) and tacrolimus (Tcr) are scarce and there were no reports that include comparisons with sirolimus (Sir). Moreover, different pharmacological, periodontal and genetic variables have been associated with gingival overgrowth (GO) in this group of subjects. Thus, this study aimed to: 1) evaluate the polymorphism (+3954 C/T) of the interleukin-1beta (IL-1â) gene in renal transplant recipients under immunosuppressive regimens based on CsA, Tcr and Sir. 2) evaluate changes in gingival status and potential pharmacological and periodontal risk variables associated with the GO in renal transplant recipients under immunosuppressive regimens based on CsA, Tcr and Sir, after mean interval time of 4 years. From a initial sample of 135 individuals (baseline BE), oral mucosa swabs were collected and used to evaluate the IL-1â polymorphism (+3954 C/T) assessed by PCR (Polymerase Chain Reaction) and restriction endonuclease digestion. GO+ and GO- subjects were compared in relation to the frequency of CC, CT, and TT genotypes, as well as C and T alleles, tro ugh Chi-squared test. After a interval time of 44.44 ± 9.96 months (27 117), 102 subjects from the initial sample, with no periodontal treatment, were re-examined (follow-up examination = FE). From this total, 89 subjects maintained the immunosuppressive regimen based on the same main agent (CsA = 23, Tcr = 31, and Sir = 35). Demographic and pharmacological data were collected from medical records. Periodontal data included plaque index and papillary bleeding index records. GO was evaluated by visual examination. Prevalence and severity of GO, as well as pharmacological and periodontal variables of interest, were compared between BE and FE examinations for the total sample and Csa, Tcr, and Sir groups through Wilcoxon and MacNemar tests. Multivariate logistic regression was used to determine variables associated with GO in FE. The first study (n = 135, CsA = 45, Tcr = 45 e Sir = 45) showed no significant difference in the distribution of CC, CT, and TT genotypes, as well as C and T alleles of IL-1â gene among GO+ and GO- subjects for the total sample neither for any immunosuppressive group. The second study (n = 89, CsA = 23, Tcr = 31 e Sir = 35) showed significantly reduced occurrence (BE = 28,1%; FE = 13,5%; p <0,001) and severity of GO (BE mean score = 3,74 ± 8,46; FE mean score = 1,43 ± 10,61; p < 0,001) for the total sample. For CsA and Tcr groups, although not significant, it was also observed a reduction in the occurrence of GO [CsA (BE = 56.5%; FE = 34.8%; p = 0.063); Tcr (BE = 19.4%; FE = 12.9%; p = 0.500)]. In addition, the severity of GO significantly decreased in CsA group (BE mean score = 7.70 ± 10.29; FE mean score = 0.78 ± 1.38; p = 0.003). In Sir group, GO reduced from 17.1% (BE) to 0.0% (FE) (p = not applicable). In FE, considering the total sample, GO was associated with papillary bleeding index (p = 0.001) and concomitant calcium channel blocker use (p = 0.029); in CsA and Tcr groups, GO was associated with papillary bleeding index (p = 0.029 and p = 0.033, respectively). This study points to the importance of pharmacological and periodontal variables associated with GO in immunosuppressive maintenance regimens among renal transplant recipients.